Secure State-Reconstruction Over Networks Subject to Attacks - Mao, Yanwen; Diggavi, Suhas; Fragouli, Christina; Tabuada, Paulo (IEEE control systems letters, 2021)
Secure state-reconstruction is the problem of reconstructing the state of a linear time-invariant system from sensor measurements that have been corrupted by an adversary. Whereas most work focuses on attacks on sensors, we consider the more challenging case where attacks occur on sensors as well as on nodes and links of a network that transports sensor measurements to a receiver. In this letter we provide necessary and sufficient conditions for the secure state-reconstruction problem to be solvable in the presence of attacks on sensors and on the network.